Balance level of elite amputee football players - Grzegorz Bednarczuk; Jolanta Marszałek; Bartosz Molik; Agnieszka Magdalena Nowak; Tania Bastos (Scientific Reports)
Abstract Football requires skills to perform passes, reception, shots and dribbling. Amputation of lower limb decrease balance, but is crucial for movement control in amputee football. Therefore, the aim of this study was to assess balance of amputee football players according to sports level, training experience, position on the pitch, type and moment of acquiring disability (from birth, during life). The study involved 66 participants of the European Amputee Football Championships. Balance was measured using stabilographic platform. Participants performed one-leg stance test (eyes open and closed). There were no differences in balance level between players of teams ranked between 1 and 7 and 8 to 14 places in the championships. Players who trained for more than 8 years had significantly better balance compared to players who trained shorter in trials with eyes closed. No differences in balance levels identified between groups according to position on the pitch. Although balance plays a significant role in open-skills sports, it seems to be an area underutilized in amputee football. Therefore, the training of this motor skills should be systematic and include balance exercises performed on stable and unstable backgrounds, with eyes open and closed, and individualized according to the players roles on the pitch.